Developing harmonised terminonological units in isiZulu and isiXhosa at Tertiary Institutions - Gola, Luvuyo-Lwe-Afrika (My University, 2020)
The development of South African indigenous languages has been a contentious topic amongst scholars and the government since the South African indigenous languages were reduced to writing during the colonial era. At the height of decolonising tertiary education, the development of South African languages has especially been highlighted in the country by both students and scholars who feel marginalized and would like for students who are not English or Afrikaans first language speakers to be catered for equally. The lack of terminology in the South African indigenous languages has proven to be a problem and hence it is taken over a decade to implement the programmes of languages of teaching and learning to be in the indigenous languages. The lack of terminology is an effect of the larger number of languages that need to be developed and therefore, this research has suggested harmonisation as an aid to resolving this issue. Harmonisation is unifying two or more mutually intelligible languages as illustrated in this research with isiXhosa and isiZulu. The word formation processes were used alongside the nomenclature systems, which were used to study and analyse the terms to be harmonised. During the harmonisation process it was found that isiXhosa and isiZulu are very similar in structure and that most of the terms are merely synonyms of each other and in some cases they appear in both languages as the same. Therefore, this research has proven that language harmonisation is feasible between these two languages and new Nguni terms were created that can be used by both the isiZulu and isiXhosa speakers. For quality assurance purposes, these terms were given to a group of students in order to verify if they are understandable, functional and relevant to the language speakers. The findings were in the affirmative.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Arts (African Languages and Linguistics) to Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, Johannesburg, 2020